Influence of alternative and conventional surface treatments on the bonding mechanism between peek and veneering resin for dental application - Villefort, Regina F.; Anami, Lilian C. [UNESP]; Campos, Tiago M. B.; Melo, Renata M. [UNESP]; Valandro, Luiz F.; von Zeidler, Sandra L. V.; Bottino, Marco A. [UNESP] (MDPI, 2021)
This study evaluated the influence of conventional and alternative surface treatments on wettability and the bond strength between polyether ether ketone (PEEK) and veneering resin. PEEK samples were randomly divided into five groups: sandblasting, tribochemical silica coating, etching with 98% sulfuric acid for 5 s, etching with 98% sulfuric acid for 30 s, and tribochemical silica coating plus heated silane. One of them was subjected to analysis by energy-dispersive X-ray spectroscopy (EDS) and ten were analyzed by goniometry (n = 5) and scanning electron microscopy (n = 5). Shear bond strength (SBS) was tested, and failure types were assessed. Data were analyzed using one-way ANOVA, followed by the Tukey and Duncan tests (all, α = 5%). Treatment with sandblasting and silica coating had the lowest SBS means (4.2 MPa and 4.4 MPa respectively), while sulfuric acid for 5 s showed the highest mean value (12.6 MPa), followed by sulfuric acid for 30 s and tribochemical + heated silane. All failures were classified as adhesive. The lowest mean contact angle was found for the polished (control) and etched group with 98% sulfuric acid for 30 s (83.9◦ ). Etching with 98% sulfuric acid for 5 s increased the SBS between resin and PEEK.
Keywords: Airborne-particle abrasion; Polyether ether ketone; Shear strength; Sulfuric acid; Wettability